Conduction system pacing on track to replace CRT? Review of current evidence and prospects of conduction system pacing - Moustafa, Ahmed T.; Tang, Anthony SL.; Khan, Habib Rehman (Frontiers in Cardiovascular Medicine, 2023)
Conduction system pacing (CSP) has been emerging over the last decade as a pacing option instead of conventional right ventricular (RV) pacing and biventricular (BiV) pacing.[1-3] Numerous case reports, some observational studies and a few randomized control trials have looked at optimum pacing strategies for heart failure (HF) with left bundle branch block (LBBB) or cases where left ventricular (LV) dysfunction is anticipated due to chronic RV pacing (RVP).[3-6] Evolution of pacing strategies from standard RVP to septal RVP, BiV pacing and now CSP have shown improving hemodynamic responses and possible ease of implantation of CSP systems. [7,8] In this review article, we review the literature on the evolution of CSP and common scenarios where it might be beneficial.